Installing Solar Power Plants in Snowbound Areas : Lessons from Himachal Pradesh, India - Goyal, Surbhi; Bhattacharya, Satyaki; Suresh, Shraddha; Goldes, Georg; Nirgudkar, Saurabh (World Bank, Washington, DC, 2021)
Are you facing the challenge of installing solar at high altitudes with difficult terrain and climatic conditions? This Live Wire recommends practices for setting up solar installations in snowbound terrain, based on the Bank’s assessment of technical requirements for setting up a 1 GW solar power project in Spiti Valley, Himachal Pradesh. Possible technical solutions include bifacial modules and passivated emitter and rear cell technology, all with fixed mounting systems. With nuanced solutions, it is crucial to train staff and optimize equipment for site-specific risks like heavy snow loads. Both utility-scale projects for export, as well as small setups for supplying local communities, could potentially benefit from such solutions.